Study of the Etiopathogenesis of Hyperacid Syndrome in Diarrheas of Various Etiologies - Anvarovich, Djumayev Akbar (American Journal of Bioscience and Clinical Integrity, 2025)
The aim of this work is to analyze the pathogenetic relationship between hyperacid syndrome and the development of diarrheal syndrome, to evaluate the role of acid-dependent mechanisms in the formation of the clinical picture, and to substantiate the need to include gastric acid production assessment in the diagnostic algorithm for chronic diarrhea. Hyperacidity is considered a condition characterized by excessive secretion of hydrochloric acid by the parietal cells of the stomach, leading to the inability of the protective mechanisms of the duodenum and pancreas to effectively neutralize acidic chyme. The entry of acidic contents into the upper sections of the small intestine causes inactivation of digestive enzymes, disruption of nutrient hydrolysis processes, and malabsorption, which is accompanied by osmotic and secretory diarrhea. The mechanisms of intestinal mucosal damage, acceleration of motility, and loss of fluid and electrolytes are described. It is emphasized that hyperacidity often remains an underdiagnosed cause of chronic diarrhea and is mistakenly interpreted as colitis or irritable bowel syndrome. It has been proven that therapy aimed at reducing acid production (proton pump inhibitors) leads to the cessation of diarrhea, which confirms the key role of the acid factor[1].